Ijarah Shar‘iyyah and Ijarah Taqlidiyyah: a juristic and comparative study - Ud Din, Syed Zia; Mohiuddin, Mohammad; Elatrash, Radwan Jamal Yousef (SCHOLARIUM EDUCATION & RESEARCH, 2025)
Ijarah (leasing or hiring) is one of the most significant contracts in Islamic jurisprudence, closely linked with economic activity and the exchange of services. This article presents a comprehensive, analytical, and comparative study of Ijarah Shar‘iyyah (Shariah-compliant Ijarah) and Ijarah Taqlidiyyah (customary or imitative Ijarah). Ijarah Shar‘iyyah refers to a contract concluded in full compliance with the Qur’an, Sunnah, consensus (Ijma), and established juristic principles, whereas Ijarah Taqlidiyyah denotes practices adopted merely through imitation of prevailing customs or precedents without proper adherence to Shariah requirements. The study discusses the definition of Ijarah, its pillars and conditions, types, objectives, and practical applications, and critically examines the nature, causes, and juristic implications of Ijarah Taqlidiyyah. The paper aims to clarify how Shariah-compliant leasing practices can be implemented in contemporary contexts and how Muslims can avoid non-compliant and imitative practices